Scaling Up Sweetpotato Through Agriculture and Nutrition in Mozambique - International Potato Center (2014)
SUSTAIN wants to achieve a better nutrition status through the production, marketing and consumption of a biofortifi ed crop: the Orange-fleshed sweetpotato. The project runs from 2013 to 2018 and covers four countries: Rwanda, Kenya, Malawi and Mozambique. In Mozambique SUSTAIN works in Manica Province in the Center and Maputo Province in the South.